Photoluminescence properties of Eu-doped WO3-Eu2(WO4)3 composites and single-phase Eu2(WO4)3 powders. Issue 2 (15th January 2022) - Kim, Ae Hui; Kang, Ji Ho; Hong, A-Ra; Park, Yong Jun; Kim, Tae Hyeong; Hong, Ji Ho; Kim, Ga Young; Yun, Tae Gwang; Jang, Ho Seong; Kim, Dong Hun
Abstract: The development of highly stable and efficient oxide-based red phosphors is urgently required for next-generation lighting devices. Herein, we report the micro/crystal structures and luminescent properties of single-phase Eu2 (WO4 )3 and Eu 3+ -doped WO3 -Eu2 (WO4 )3 composite phosphors prepared by a one-step conventional solid-state reaction method in air atmosphere. As increasing Eu contents in the mixtures of WO3 and Eu2 O3, the intensities of the X-ray diffraction peaks of Eu2 (WO4 )3 increased while that of WO3 decreased. The photoluminescence intensity of the synthesized phosphors increased with increase in the Eu content when calcined at 900 °C, while it degraded at a higher temperature. Red-emitting single-phase Eu2 (WO4 )3 powders were successfully obtained when the WO3 and Eu2 O3 powders were calcined in the ratio of 3:1. The intensity of the red emission spectra of the Eu2 (WO4 )3 phosphor was higher than those of the 6, 12, and 24 at.% Eu-added WO3 composites at excitation wavelengths of 394 and 465 nm. On the other hand, the intensity of emission from the single-phase phosphor was lower than that of the Eu-doped WO3 -Eu2 (WO4 )3 composites under excitation of UV light at 254 nm. Thus, we propose two prospective phosphors for application as red phosphors at various wavelengths.